Solute concentration effects on microstructure and the compressive strength of ice‐templated sintered lithium titanate. Issue 11 (13th July 2022) - Parai, Rohan; Nie, Ziyang; Hempley, Raina; Koenig, Gary M.; Ghosh, Dipankar
Abstract: This work investigated the role of sucrose and cationic dispersant (1‐hexadecyl)trimethylammonium bromide concentration on ice‐templated sintered lithium titanate microstructure and compressive strength, to enable a comprehensive understanding of composition selection and elucidate processing–microstructure–mechanical property relationships. Sucrose and dispersant concentrations were varied to change total solute concentration in suspensions and viscosity. Dispersant was more effective in reducing viscosity than sucrose; however, their combination had an even greater impact on reducing viscosity. Based on viscosity measurements, a total of 12 suspension compositions were developed, and materials were fabricated at two different freezing front velocity (FFV) regimes. Solute concentration greatly influenced ice‐templated microstructure and microstructure development improved with solute concentration. Depending on solute concentration, type of solute, viscosity, and FFV, a wide variety of microstructures were observed ranging from lamellar to dendritic morphologies. Solute concentration effect was rationalized based on solid–liquid planar interface instability. For suspensions with comparable viscosity, solute concentration can be varied to tune microstructure, whereas for suspensions with comparable solute concentration, viscosity variation can tune microstructure. Compressive strength of sintered materials generally increased with total solute concentration, sucrose concentration, viscosity, and FFV. Due to the wide variety of microstructure, strength also varied over a wide range, 23–128 MPa. Abstract : Development of ice‐templated microstructure in LTO materials was dependent on total solute concentration, type of additive, viscosity, and freezing front velocity. Viscosity of suspensions depended on total solute concentration and type of solute. Compressive strength increased with total solute concentration.